Points of Convergence in Music Education: The Use of Data Labels as a Strategy for Mixed Methods Integration. (July 2016) - Fitzpatrick, Kate R.
Although the mixing of quantitative and qualitative data is an essential component of mixed methods research, the process of integrating both types of data in meaningful ways can be challenging. The purpose of this article is to describe the use of data labels in mixed methods research as a technique for the integration of qualitative and quantitative data within equivalent-status mixed methods research designs. The music education study described utilized a combination of focus group, survey, and case study data to provide a fuller view of instrumental music teaching within the urban context. Using this study as an exemplar, the author discusses the application of data labels to points of convergence between qualitative and quantitative strands of mixed methods studies in order to achieve integration between both data sets.